1986
DOI: 10.1007/bf00698791
|View full text |Cite
|
Sign up to set email alerts
|

Undulating course of nerve fibres and bands of Fontana in peripheral nerves of the rat

Abstract: The undulating course of nerve fibres and the optical effect of that course, i.e. the bands of Fontana, were studied in the peripheral nerves of the adult rat using light microscopy. The arrangement of collagen fibres in the endoneurium of these nerves was evaluated using transmission and scanning electron microscopy. No nerve fibres undulation was noted on the intracranial sections of the cranial nerves or on the spinal roots. In their endoneurium a few, irregularly arranged collagen fibrils were found. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 7 publications
2
32
0
Order By: Relevance
“…Previous studies reported that when a nerve is stretched using longitudinal tensile stress, the nerve fibers start losing their undulation and the appearance of the bands begins to fade. 33,34 Similar phenomena were also observed in this study. Representative image and plot for stretched nerve in Fig.…”
Section: Quantitative Evaluation Of Bands Of Fontanasupporting
confidence: 91%
See 4 more Smart Citations
“…Previous studies reported that when a nerve is stretched using longitudinal tensile stress, the nerve fibers start losing their undulation and the appearance of the bands begins to fade. 33,34 Similar phenomena were also observed in this study. Representative image and plot for stretched nerve in Fig.…”
Section: Quantitative Evaluation Of Bands Of Fontanasupporting
confidence: 91%
“…[32][33][34] Owing to the undulating nature of nerve fibers inside the bundle, dark and light stripes become visible on the surface of the fascicule when light is reflected back from the nerve. Their visibility depends both on the degree of nerve stretching and on the angle of illumination.…”
Section: Visualization Of Bands In Volumetric Oct Imagesmentioning
confidence: 99%
See 3 more Smart Citations